Photochemical Degradation of a Phenyl-urea Pesticide Chlorotoluron - Zemanová, Martina (Jihočeská univerzita, 2008)
Chlorotoluron photochemical degradation in homogeneous phase (aqueous solutions) was studied. Photolysis by UV radiation, influence of metal (ferric, ferrous) ions, pH, and solvent composition on the reaction rate was investigated. Photosensitizing effect of humic samples was tested. Kinetic characteristics (rate constants, overall quantum yield), products of reactions and extent of mineralization was evaluated.
Photochemical Degradation of a Phenyl-urea Pesticide Chlorotoluron
Keywords: chlorotoluron; phenyl-urea pesticide; photochemical degradation; chlorotoluron; phenyl-urea pesticide; photochemical degradation